Investigating the physical stability of repackaged medicines stored into commercially available multicompartment compliance aids (MCAs). Issue 2 (8th May 2017) - Raimi‐Abraham, Bahijja Tolulope; Garcia del Valle, Alba; Varon Galcera, Carlota; Barker, Susan Anne; Orlu, Mine
Abstract: Background: Compliance aids are devices which have been developed and are currently used to assist individuals in their medicines management. The use of compliance aids involves the transfer of medicines from the manufacturers' original packaging and repackaged into an multicompartment compliance aid (MCA). MCAs do not guarantee the same level of protection compared to manufacturer's original packaging. Objective: The aim of this study was to investigate the stability profile of atenolol, aspirin and lansoprazole dosage forms repackaged together in two different commercially available MCAs. Methods: In a laboratory in the United Kingdom, the physical stability of the formulations repackaged into two commercially available brands of MCAs was evaluated. After 8 weeks of storage (under controlled ambient conditions), changes in the disintegration (tablets only) and dissolution properties (all formulations) were examined in accordance with British Pharmacopoeia (BP) specifications. Key findings: Findings from this study confirm that changes in solid‐dosage form quality are observed when repackaged into MCAs compared to manufacturers packaging resulting in differences in in‐vitro dissolution performance. However, even with these changes, overall product performance was acceptable and within BP specifications. Conclusion: There is a need for greater collaboration in this area between manufacturers, hospital and community pharmacists, academics and policymakers to increase the data available on the physical stability and in turn performance of medicines repackaged into MCAs.